FUNCTIONALITY AND ROLE OF MANAGERS IN INCREASING THE FINANCIAL PERFORMANCE OF SHARIA BANKING - Yulfiswandi Yulfiswandi; Dessy Aliandrina; Muhammad Rivaldy Hisham; Dewi Kurniawaty; Maidan Setiawati (Journal of Global Business and Management Review, 2023)
The stock price determines the company's value and sound company operations. Suppose the company's operations are going well. In that case, the company's value also has a good effect on what is regulated in management with the scientific problems companies face. The manager's role in managing the company's organization in achieving the company's goals makes the knowledge used by the company, such as planning, organizational structure, and decision making, as well as managers in providing communication, influence from leadership, direction, control, evaluation and assessment. In this study, the authors used the literature study method to obtain secondary data to analyze managers' roles and influences on improving Islamic banking finance.